Policy and Oversight of Cardiac Transplantation - Amit Alam; Shelley Hall (Methodist DeBakey Cardiovascular Journal)
The first heart transplantation in the United States was performed in 1968. The first national heart allocation system was developed two decades later in 1988 as a two-tiered system. Our current heart allocation system, adopted in 2018 as a six-tiered system, is evolving to become a continuous distribution model. Herein, we review the history of the Organ Procurement and Transplantation Network, the evolution of the cardiac allocation system, modern day challenges of the current heart allocation system policy, and the future of transplantation given ongoing implementation of the modernization initiative.